A New Invasive Method of Continuously Monitoring Myocardial Ischemia in Interventional Cardiology – Electrocardiography from the Coronary Sinus - Shevchenko, Yury L.; Ermakov, Dmitry Y. (Cardiology and Cardiovascular Medicine, 2020)
Background The aim of this work is to assess the ability to control myocardial ischemia (MyI) using a method of unified Electrocardiography from the coronary sinus (ECGCS). Materials and methods This study included 88 patients with single-vessel lesions of different coronary arteries (CA) who had a 10-channel EE installed into their coronary sinus (CS) during percutaneous coronary intervention (PCI). Ischemia was monitored by an electrophysiological recording system (EPRS) with the following settings: electrode consolidation into five cathode-anode pairs with a frequency range of 30–500 Hz, a cutoff of 1-cm signal, and an amplitude of 0.3 mV/cm. ROC analysis determined the method sensitivity and specificity for different cut-off points. Results According to ECG-CS, at maximum ischemic exposure (during stent implantation), the average ST segment deviations from the isoline were: with ADA intervention – depression in CS leads 1-2 – 0.12±0.03 mV, CS 3-4 – 0.1±0.02 mV; elevation – 0.14±0.04 mV and 0.11±0.02 mV, respectively; LCX – ST depression in CS leads 3-4 – 0.11±0.02 mV, CS 5-6 – 0.11±0.02 mV; elevation – 0.12±0.02 mV and 0.15±0.03 mV, respectively; RCA – ST depression in CS leads 7-8 – 0.1±0.01 mV, CS 9-10 – 0.12±0.02 mV; elevation – 0.13±0.02 mV, and 0.14±0.03 mV, respectively. The ECG-CS method sensitivity according to ROC analysis in the case of ST depression was 79.5%, specificity 100%; for ST elevation – 83% and 100%, respectively. Conclusion ECG-CS is an effective, highly informative and promising new method of invasive MyI control in interventional cardiology.